Enhanced immunity and hemocytes proliferation by three immunostimulants in tri-spine horseshoe crab Tachypleus tridentatus. Issue 115 (August 2021) - Liu, Ximei; Xu, Zhen; Chang, Xueqing; Fang, James K.H.; Song, Jie; He, Jinfeng; Tai, Zongguang; Zhu, Quangang; Hu, Menghong
Abstract: Tachypleus amebocyte lysate (TAL) is crucial in medical testing, but its industry in China has been restricted due to the decline of horseshoe crab population in recent years. Exploring methods of enhancing immunity and rapid hemocytes proliferation is urgent for the industrial horseshoe crab culture. In this study, β-glucan (G), peptidoglycan (P), and squalene (S) were injected to horseshoe crabs at two concentrations (5 and 10 mg/kg), in order to compare their effects on total hemocyte count (THC), reactive oxygen species (ROS), and non-specific immune enzyme activities. Results showed that the THC, superoxide dismutase (SOD), catalase (CAT), and total antioxidant capacity (T-AOC) were significantly increased by three immunostimulants at different points of time; ROS was significantly increased except at two squalene groups; lysozyme (LZM) and alkaline phosphatase (AKP) activity were increased except at low dose (5 mg/kg) squalene group; malondialdehyde (MDA) activity was decreased in all treatments; and hemocyanin concentration (HC) changed little during the experiment. At the 48th hour, THC, ROS, SOD, CAT, T-AOC, LZM, and AKP activities were significantly higher in the two peptidoglycan groups than those in the control group; the low dose β-glucan and squalene groups showed significantly higher SOD and CAT, but their THC and AKP were not significantly different from those of the control group. In general, all three immunostimulants stimulated the hemolymph parameters of horseshoe crabs, notably, peptidoglycan could significantly increase the THC and enzyme activities, suggesting that peptidoglycan can be developed as an efficient immunostimulant for horseshoe crabs. Highlights: First report on the effect of immunostimulants on hemocytes proliferation of Tri-spine horseshoe crab. β-glucan, peptidoglycan, and squalene enhanced hemocytes proliferation and immune functions of adult horseshoe crabs. Peptidoglycan is superior to β-glucan and squalene to be developed as an immunostimulant for horseshoe crabs.